1997
DOI: 10.1007/s003840050084
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the pharmacological manipulation of postoperative intestinal motility on colonic anastomoses

Abstract: The use of metoclopramide (a gastrointestinal prokinetic agent) during the early postoperative period was associated with an increase in dehiscence in colonic anastomosis and, when animals survived, there was a significant decrease in anastomotic resistance. Hyoscine (an inhibitor of gastrointestinal motility) did not improve the healing of anastomoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 0 publications
2
25
1
2
Order By: Relevance
“…García-Olmo et al 16 evaluated the effects of pharmacological manipulation of gastrointestinal motility on the resistance of colonic anastomoses and concluded that treatment with metoclopramide was associated with fewer adhesions to the anastomosis and a significant decrease in anastomotic resistance four days after surgery. In another study 17 , metoclopramidetreated animals showed adhesion formation within the abdominal cavity and in the anastomosis similar to that of animals receiving saline three and seven days after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…García-Olmo et al 16 evaluated the effects of pharmacological manipulation of gastrointestinal motility on the resistance of colonic anastomoses and concluded that treatment with metoclopramide was associated with fewer adhesions to the anastomosis and a significant decrease in anastomotic resistance four days after surgery. In another study 17 , metoclopramidetreated animals showed adhesion formation within the abdominal cavity and in the anastomosis similar to that of animals receiving saline three and seven days after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…García-Olmo et al 8 conducted a study to determine the pharmacological effects of manipulating gastrointestinal motility on the resistance of colic anastomosis. The authors concluded that the use of metoclopramide immediately after operation was associated with a significant increase in colonic anastomotic dehiscence and, in the surviving animals, a significant decrease in anastomosis resistance.…”
Section: Introductionmentioning
confidence: 99%
“…No trato gastrintestinal, ele está localizado principalmente na submucosa. Para que se mantenha a resistência mecânica da parede intestinal é necessário que ocorra um equilíbrio no processo de lise e de síntese do colágeno, fato este que ocorre na parede do intestino normal 7,15,16,17 e que pôde ser demonstrado no estudo aqui apresentado na avaliação histológica.…”
Section: Grupounclassified